Analysis and Research on the Influence of Civil Aircraft System on CO2 Emission - Sun Kexin; Yang Yi; Xuan Zhaojie (E3S Web of Conferences)
Based on the international standard ICAO Annex 16 Volume III, this paper adopts the CO2 emission airworthiness calculation method proposed by ICAO to carry out sensitivity analysis and research on the influence of air intake volume of pneumatic system, power extraction of electric system and hydraulic system from engine on civil aircraft CO2 emission. The methods of reducing fuel consumption and CO2 emission of aircraft are discussed from the perspective of air intake volume and power extraction.